THE FACTORS ASSOCIATED WITH ALLERGIC RHINITIS IN THE DYSPHONIC PROFESSIONAL VOICE USERS - simovic, sladjana stanimir (Medicinski časopis, 2018)
Objectives: Aim of the present study was to investigate the frequency of allergic rhinitis in disphonic professional voice users and to assess the correlation between allergic rhinitis and demographic characteristics (sex, ages and years in occupation) and presence of laryngopharyngeal reflux, as comorbidity health condition. Methods: A total of 104 patients (17 male, 87 female) with mean age of 36,8±10,9 years were included in the study. The patients underwent rigid or transnasal laryngoscopy with videostroboscopy which revealed the presence of glottic insufficiency and hyperkinetic dysphonia, respectively, in 39,4% and 22,1%. Descriptive analysis, Pearson Chi-Square Tests and Binary Logistic regression were carried out using the SPSS 13.0 statistical software package. Results: Frequency of allergic rhinitis in disphonic professional voice users was 44,2%. The patients were 1.1 times more likely to have allergic rhinitis with each passing year of life. Allergic rhinitis is with each year in occupation 0,89 times less frequent and 0,035 times less often in patients with gastro-oesophageal reflux disease. Conclusions: These results imply the need to consider allergic rhinitis as important predisposing factor for disphonia in professional voice users. Keywords: allergic rhinitis, dysphonia, predisposing factors, professional voice users. Keywords: rhinitis, allergy, dysphonia, voice.